High coincidence-to-accidental ratio continuous-wave photon-pair generation in a grating-coupled silicon strip waveguide. (25th May 2017) - Guo, Kai; Christensen, Erik N.; Christensen, Jesper B.; Koefoed, Jacob G.; Bacco, Davide; Ding, Yunhong; Ou, Haiyan; Rottwitt, Karsten
Abstract: We demonstrate a very high coincidence-to-accidental ratio of 673 using continuous-wave photon-pair generation in a silicon strip waveguide through spontaneous four-wave mixing. This result is obtained by employing on-chip photonic-crystal-based grating couplers for both low-loss fiber-to-chip coupling and on-chip suppression of generated spontaneous Raman scattering noise. We measure a minimum heralded second-order correlation of, demonstrating that our source operates in the single-photon regime with low noise.